Cybervictimization, Depression, and Adolescent Internet Addiction: The Moderating Effect of Prosocial Peer Affiliation - Wang, Zhenhai; Xie, Qi; Xin, Mucheng; Wei, Chang; Yu, Chengfu; Zhen, Shuangju; Liu, Sha; Wang, Jianping; Zhang, Wei (Frontiers in Psychology, 2020)
Although vast research has shown that cybervictimization is a significant risk factor of adolescent’s internet addiction (IA), little is known about the mediating and moderating mechanisms behind this relationship. The current study examined whether depression mediated the relationship between cybervictimization and adolescent’s IA, and whether the direct and indirect effect was moderated by prosocial peer affiliation (PPA). A sample of 1,006 adolescents (Meanage = 13.16; SD = 0.67) anonymously completed the questionnaires. The results revealed that the positive association between cybervictimization and adolescent’s IA was mediated by depression. Moderated mediation analysis further showed that PPA moderated the association between cybervictimization and adolescent’s IA. However, this indirect effect was stronger for adolescents with high PPA than for those with low PPA, which means that the protective effects of PPA are limited. These findings highlight the mediating and moderating mechanisms between cybervictimization and adolescent’s IA, and provide guidance for the prevention and intervention in adolescent’s IA.